Workplace readiness for health occupations : a foundation for excellence - Colbert, Bruce J. (Albany, NY : Delmar Publishers, 2000)
Discusses and helps develop the attitudes and skills necessary to succeed in the health care professions.
Includes index.
Keywords: Medicine -- Vocational guidance; Medicine -- Vocational guidance; Vocational guidance